Finding Nemo: Verne’s antihero as original steampunk - Perschon, Mike (My University, 2023)
This volume is a fresh examination of the works of Jules Verne, the pioneering and enduringly popular science fiction writer. Essays study Verne’s various novels—including Around the World in Eighty Days, The Mysterious Island and The Adventures of Captain Hatteras. Included essays offer analyses of literary responses to Verne’s work, assessments of film adaptations of his novels and discussions of steampunk, the Verne-inspired science fiction subgenre that has influenced writers like Philip Jose Farmer, Caleb Carr and Adam Roberts.
Keywords: Jules Verne; criticism and interpretation; steampunk